Effect of palm oil fuel ash pofa)with limestone as a partial cement replacement material towards compressive strength and corrosion resistance - Farah Zafirah, Mod Ma'asum (2015)
Malaysia is a country with a lot of agricultural products that can be used to increase Malaysia’s economy. With the growing concern nowadays about the problem of pollution together with the increasing level of waste product from the factory, many researchers were focusing on how to maximizing the utilization of agricultural and industrial waste. One of the by-products was palm oil fuel ash (POFA). POFA is the grey stuff with seem black which an agro-waste resulting from the incineration process at temperature about 800⁰C - 1000⁰C of oil palm residue. POFA will acts as a natural pozzolana in a partial replacement of cement. This can be done together with the addition of limestone. For this research, the relationship when there is an addition of limestone as a partial cement replacement material in concrete and where there is only POFA as pozzolana was investigated. The aim of the study is to investigate the effect of POFA with limestone as a partial cement replacement material in term of concrete compressive strength and corrosion resistance. Ordinary Portland Cement (OPC) has been partially replaced with 20% of POFA only and 20% POFA with 5% and 10% of limestone respectively. For compressive strength test, cube sample of 150mm × 150mm × 150mm that were cured for 7, 28 and 90 days have been used. As for the water permeability test, cube sample of 100mm × 100mm × 100mm that were cured for 28 and 60 days have been used. Cylinder in the form of 80mm in diameter and 160mm height and were cured for 28 days has been used for impressed voltage test. For the compressive strength test, the control without any replacement of cement shows the highest strength. As for the permeability test, the control shows the highest permeability of concrete but in impressed voltage test, concrete with 20% partial replacement of cement with POFA shows the same reading as control. As a conclusion, it is found that replacement of cement with 20% of POFA can reduce the corrosion but not in compressive strength and water permeability of concrete.